Nailūang khō̜ng rao - Ngāmphan Wētchāchīwa (Samnakngān Sœ̄msāng ʻĒkkalak khō̜ng Chāt, Samnakngān Palat Samnak Nāyok Ratthamontrī, 2012)
Life and accomplishments of Bhumibol Adulyadej, King of Thailand; volume commemorating his 84th birth anniversary on December 5, 2011.